Internal audit effectiveness in zakat institution from perspective of auditee / Noraini Shamsuddin ... [et al.] - Shamsuddin, Noraini; Zaini, Ju Anizai; Mustaffha, Nazifah; Johari, Norhanizah (Accounting Research Institute (ARI), Universiti Teknologi MARA, Shah Alam, 2018)
Internal audit function (IAF) is one of the most important meanings for management to confirm and verify the compliance of administrative units in the financial and administrative policies, legislations, financials and administrative systems as well as the adoption of public policies. IAF also helps in running an organization more efficiently and effectively to increase stakeholders' value. Moreover, with growing size and attention given to the zakat institutions in the recent years, it has made an increase importance of IAF. Due to the importance of IAF, this paper aims to identify the perceived effectiveness of internal audit department (IAD) in zakat institutions (ZI) from auditees' perspective to assist on close cooperation and necessary improvement in the IAF. To develop the understanding of the factors that lead to effectiveness of IAD, this paper used qualitative method which is semi-structured interview auditees from four selected ZIs in Malaysia. Each ZIs was represented by two auditees from two different department. There are two factors explored, namely organizational status and competency of IAD. The findings show that both factors are important to achieve the effectiveness of IAF. Additionally, most of the auditees (ZI1, ZI2 and ZI3) agreed that management support are the main factors affecting the IAD effectiveness. Meanwhile, ZI4 perceived that training is the main factor contributing to the same effectiveness. It is hoped that the findings are able to increase the awareness among ZI's auditors and management to improve the IAD effectiveness in the future.